Introducing Peer-supported Open Dialogue in changing mental health care - Lorenz-Artz, Karin; Bierbooms, Joyce; Bongers, Inge (Frontiers in Psychology, 2023)
The need to transform the mental health care towards person-centered, recovery-based and network-oriented care is recognized worldwide. Open Dialogue (OD) is seen as a hopeful approach for this change and is introduced in countries around the globe. Five Dutch mental health care organizations spread over the Netherlands introduced the Peer-supported Open Dialogue (POD) approach, which is similar to OD but includes an explicit role of peer support workers. However, adoption appears to be stagnating as pod-trained professionals struggle to explain in a comprehensive way to traditional care what POD is and entails in the Dutch context. This study describes the shared meaning and integrated vision on the POD approach in the Dutch setting. In doing so, it becomes more transparent how the approach fits within the Dutch context and POD becomes more understandable for professionals who are not POD trained. This can increase the chance of a wider adoption amongst mental health care professionals. Furthermore, we hope that this narrative contributes to the further development of the POD approach and the current discourse about the needed transformation of the mental health care context. We present the results of 29 interviews and 1 focus group with Dutch POD-trained professionals with different professional backgrounds working in mental health care practices. Our findings show that within the Dutch shared meaning and integrated vision of the POD approach, four aspects contribute to making the approach more comprehensible for not POD trained professionals : 1) describing first the innovative core aspect of POD followed by organizational elements, 2) highlighting the elements ‘presence’, ‘reflecting’ and ‘expertise by experience’, 3) conceptualizing the main elements and 4) adjusting two terms to better fit the Dutch context. In addition, the (shared vision on) POD approach gives meaning to the needed transformation of the (Dutch) mental health care on two intertwined areas: the paradigm shift and the reshaping of the mental health care. In this manner, the shared meaning and integrated vision on the POD approach presents an example of how the (Dutch) mental health care could transform towards person-centered, recovery-based and network-oriented care.